PERBEDAAN UKURAN GIGI MOLAR PERTAMA MAKSILA DAN KANINUS MANDIBULA PERMANEN ANTARA MAHASISWA LAKI-LAKI DAN PEREMPUAN (Tinjauan pada Mahasiswa PSKG Suku Banjar) - Siti Aulia Rahmah; Bayu Indra Sukmana; Irnamanda D.H (Universitas Lambung Mangkurat, 2024)
ABSTRACTBackground: Natural disasters occur frequently in Indonesia. Gender identification is one of the important things in determining the identity of the victim. Gender can be identified based on the size of the teeth. Differences in tooth size are caused by differences in gender and race. Objective: To determine mean difference in the size of maxillary first molar teeth and mandibular caninus between males and females in Banjar tribe PSKG students. Methods This research is a analytic observational method. This study used 40 male and 40 female dental models that measured the mesiodistal and buccolingual width of the maxillary first molar and mandibular canine teeth using digital caliper. Results: The results of the normality test of normally distributed data, followed by an independent t-test, obtained a p value = 0.0001 <0.05 which shows that the hypothesis is accepted or there is a significant difference in the size of the mesiodistal and buccolingual teeth in the maxillary first molar and mandibular canine between male and female students of the Banjar tribe. Conclusion: There is a difference in the mesiodistal and buccolingual means of maxillary first molar and mandibular canine teeth between males and females in Banjar tribe PSKG students.Keywords: Sex identification, tooth size, mesiodistal, buccolingual, maxillary first molar, mandibular caninus ABSTRAKLatar Belakang : Bencana alam sering terjadi di Indonesia. Identifikasi jenis kelamin adalah salah satu hal penting dalam menentukan identitas korban. Jenis kelamin dapat diidentifikasi berdasarkan ukuran gigi geligi. Perbedaan ukuran gigi disebabkan oleh adanya perbedaan jenis kelamin dan ras. Tujuan: Untuk mengetahui perbedaan rerata ukuran gigi molar pertama maksila dan kaninus mandibula antara laki-laki dan perempuan pada mahasiswa PSKG suku Banjar. Metode: Penelitian ini merupakan metode observasional analitik. Penelitian ini menggunakan 40 model gigi laki-laki dan 40 model gigi perempuan yang diukur lebar mesiodistal dan bukolingual gigi molar pertama maksila dan kaninus mandibula menggunakan kaliper digital. Hasil: Hasil uji normalitas data berdistribusi normal, dilanjutkan dengan uji t-test independent didapatkan nilai p=0.0001<0.05 yang menunjukkan hipotesis diterima atau terdapat perbedaan signifikan ukuran gigi mesiodistal dan bukolingual pada gigi molar pertama maksila dan kaninus mandibula antara mahasiswa laki-laki dan perempuan suku Banjar. Kesimpulan: Terdapat perbedaan rerata ukuran gigi mesiodistal dan bukolingual pada gigi molar pertama maksila dan kaninus mandibula antara laki-laki dan perempuan pada mahasiswa PSKG suku Banjar. Kata kunci: Kaninus Mandibula, Bukolingual, Mesiodistal, Maksila, Jenis Kelamin, Ukuran Gigi.